The double-edged sword effect of empowering leadership on illegitimate tasks: role boundary redefinition and individual differences - Yang, Qin; Jin, Zhijun; Shao, Jing; Guo, Fang; Huang, Xujuan; Wenjie, Yin; Wang, Yu (Frontiers in Psychology, 2026)
In contemporary organizations, employees often encounter illegitimate tasks, which violate their professional role expectations and undermine their occupational identity. Drawing on role theory and the Job Demands–Resources (JD-R) model, this study investigates how empowering leadership influences perceptions of illegitimate tasks through role boundary redefinition. Analysis of survey data from 354 corporate employees reveals that empowering leadership reduces perceptions of illegitimate tasks by enhancing work passion, while increasing them through elevated role stress. Furthermore, regulatory focus moderates these relationships: promotion focus strengthens the link between empowering leadership and work passion, while prevention focus amplifies the association between empowering leadership and role stress. The study underscores that perceptions of illegitimate tasks are subjective and shaped by the dynamic renegotiation of role boundaries initiated by empowering leadership, with individual differences, particularly regulatory focus, influencing whether employees perceive these tasks as growth opportunities or burdens that exceed their role expectations.